Hybrid laparoscopic repair of complex abdominal wall hernias with transabdominal partially extraperitoneal mesh fixation: preliminary results - Mahmood, Sarah; Moollan, Yusuf; Badiani, Sarit S.; Berney, Christophe R. (Frontiers in Surgery, 2025)
BackgroundThere are two conventional approaches to abdominal wall hernia repairs that aim to achieve anatomical restoration. Open approaches have the advantage of complete hernial sac excision with freedom of mesh placement. In comparison, the advantages of the laparoscopic approach involve shorter hospital stays, less postoperative pain, and fewer postoperative complications. More recently, the hybrid approach, which combines the two techniques, has gained popularity as a way to potentially reap the benefits of both. Our aim was to determine whether this hybrid approach can achieve the same benefits, irrespective of hernia size, age, and body mass index (BMI). Primary outcome of interest was hernia recurrence. Secondary outcomes included postoperative complications, pain, and quality of life (QoL).MethodMedical records of all patients who underwent hybrid laparoscopic hernia repair (HLHR) with transabdominal partially extraperitoneal (TAPE) mesh fixation between 2017 and 2023 were retrieved from a prospectively maintained institutional database and retrospectively analyzed. Intra- and postoperative complications, as well as hernia recurrence, were recorded. QoL was assessed using the Carolinas Comfort Scale (CCS).ResultsThere were 37 patients (21 women, 56.8%) with a mean age of 66 years and BMI of 34.2 kg/m2 who underwent hybrid hernia repair. Of them, 34 (91.9%) were incisional hernias, of which 50% were recurrent. Mean hernia defect size was 96.8 cm2. Of the patients, 12 (32.4%) received preoperative chemical component separation with botulinum toxin A (BTA); this group had a significantly higher BMI and hernia size compared to the no BTA group (37.7 vs. 32.5; p = 0.048; 174.5 cm2 vs. 59.5 cm2; p = 0.0002). There were no intraoperative complications; however, there were 8 (21.6%) minor postoperative complications. After a mean follow-up of 40 months, we recorded one hernia recurrence at 23 months postoperatively (2.7%). In addition, out of 29 (78.4%) patients assessed for QoL, the median and mean scores were reported as 0 out of 115 and 2.6 out of 115 points scale, respectively.ConclusionsHLHR with TAPE mesh fixation is safe, with satisfactory mid- to long-term outcomes, irrespective of hernia size and BMI.